2018
DOI: 10.1111/ans.14724
|View full text |Cite
|
Sign up to set email alerts
|

Does inferior mesenteric artery ligation affect outcome in elective colonic resection for diverticular disease?

Abstract: No differences were observed in surgical outcome in IMA ligation and preservation groups, particularly preservation or ligation of the IMA did not affect leakage rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 22 publications
(23 reference statements)
0
17
1
Order By: Relevance
“…The methodological evaluation of the non‐RCTs with the MINORS scale showed that two studies scored 21 points (high quality) , two had 17 points and the other two studies scored 10 points (poor quality) (Appendix ). In the non‐RCTs there was a possible selection bias associated with the decision to preserve or to ligate the IMA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methodological evaluation of the non‐RCTs with the MINORS scale showed that two studies scored 21 points (high quality) , two had 17 points and the other two studies scored 10 points (poor quality) (Appendix ). In the non‐RCTs there was a possible selection bias associated with the decision to preserve or to ligate the IMA.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic search strategy identified 145 citations. After the initial screening of the titles and abstracts and removal of duplications, 58 titles remained, of which 15 were considered relevant [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. A total of eight studies met the inclusion criteria and were included in the analysis [16][17][18][19][20][21][22][23] and seven studies were excluded [24][25][26][27][28][29][30] (see Appendix S1 in the online Supporting Information).…”
Section: Results Of the Searchmentioning
confidence: 99%
See 3 more Smart Citations